The Effect Of Price, Promotion Social Media And Product QualityOn Income Business Of Screen Printing 289 Farhan Design - Hanif, Irsyad Farhan; Zebua, Yuniman; Pitriyani, Pitriyani (International Journal of Science, Technology & Management, 2022)
289 Farhan Design's screen printing business which is currently developing is aware of the importance of strategy in winning market competition. This study aims to determine the effect of price, promotion through social media and product quality on screen printing business income 289 farhan designs. The sample in this study were 66 customers who used 289 Farhan Design's screen printing business services using a total sampling technique. The variables used in this study consisted of Price (X1), Social Media Promotion (X2), Product Quality (X3) as the independent variable and Income (Y) as the dependent variable. The data analysis technique in this study used the multiple linear regression method. The results of this study indicate that price, social media promotion and product quality have a positive and significant effect on the revenue of the 289 farhan design screen printing business, while the price has a positive but not significant effect on the screen printing business income of 289 farhan design.